2004
DOI: 10.1152/ajplung.00188.2003
|View full text |Cite
|
Sign up to set email alerts
|

Matrix GLA protein modulates branching morphogenesis in fetal rat lung

Abstract: . Matrix GLA protein modulates branching morphogenesis in fetal rat lung. Am J Physiol Lung Cell Mol Physiol 286: L1179 -L1187, 2004 10.1152/ajplung. 00188.2003.-The regulation of matrix ␥-carboxyglutamic acid protein (MGP) expression during the process of lung branching morphogenesis and development was investigated. MGP mRNA expression was determined over an embryonic and postnatal time course and shown to be developmentally regulated. Immunohistochemical analysis revealed increased staining for MGP in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…5B). We also found that Habc-EPM and Habc132 increased gene expression of a number of additional transcripts encoding molecules known to be involved in branching morphogenesis, including Fas (31) and matrix GLA protein (32) (Fig. 5B).…”
Section: Resultsmentioning
confidence: 62%
“…5B). We also found that Habc-EPM and Habc132 increased gene expression of a number of additional transcripts encoding molecules known to be involved in branching morphogenesis, including Fas (31) and matrix GLA protein (32) (Fig. 5B).…”
Section: Resultsmentioning
confidence: 62%
“…Pulmonary expression of MGP starts to increase after E14 (20), which coincides with an exponential increase in vascular networks (21). To examine if a branching defect led to the abnormal vasculature in the MGP transgenics, we examined the pulmonary vessels in non-perfused E15.5 and E18.5 embryos.…”
Section: Resultsmentioning
confidence: 99%
“…MGP expression is observed throughout lung morphogenesis. It has been localized to the submucosal layers in the developing respiratory tract in mice (57), and has been associated with lung branching (58,59). TGF-␤ and VEGF are both involved in the development and maintenance of lungs (10,60), where correct spatial and timely expression of TGF-␤, TGF-␤ receptors, and VEGF is crucial for morphogenesis.…”
Section: Figmentioning
confidence: 99%